2022
DOI: 10.3389/fonc.2022.953884
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and microbial factors affect the prognosis of anti-pd-1 immunotherapy in nasopharyngeal carcinoma

Abstract: Antibodies targeting the programmed cell death protein-1 (PD-1) molecule have been reported to hold promising antitumor activities in patients with nasopharyngeal carcinoma (NPC). However, only a small subset of NPC patients benefits from the anti-PD-1 monotherapy and factors that affect the treatment response need further investigation. This study aimed to examine the impact of multiple genetic and environmental factors on outcome of anti-PD-1 immunotherapy by identifying tumor size, tumor mutation burden (TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…A previous study showed that patients with type 2 diabetes had higher Erysipelotrichaceae levels than patients with normal glucose tolerance [ 41 ]. There is growing evidence showing the adverse roles of Erysipelotrichaceae and Erysipelatoclostridium play in host lipid metabolism [ 42 ], immune response [ 43 ], inflammation [ 44 ], depression [ 45 ], metabolic-associated fatty liver disease [ 46 ], cancer [ 47 ], and response to cancer immune therapy [ 48 , 49 ]. However, in a human-based study, increased physical activity was associated with a higher relative abundance of Erysipelotrichaceae [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that patients with type 2 diabetes had higher Erysipelotrichaceae levels than patients with normal glucose tolerance [ 41 ]. There is growing evidence showing the adverse roles of Erysipelotrichaceae and Erysipelatoclostridium play in host lipid metabolism [ 42 ], immune response [ 43 ], inflammation [ 44 ], depression [ 45 ], metabolic-associated fatty liver disease [ 46 ], cancer [ 47 ], and response to cancer immune therapy [ 48 , 49 ]. However, in a human-based study, increased physical activity was associated with a higher relative abundance of Erysipelotrichaceae [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, tumor mutational burden (TMB) was found to be correlated with clinical responses to anti-PD-1 therapy in most solid tumor ( 23 , 24 ). A recent study by Zhang reported that NPC patients with high TMB displayed improved clinical responses to anti-PD-1 therapy, as measured by PFS ( 25 ). Therefore, these patients were more likely to be highly aggressive and more likely to benefit from immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The importance of specific bacterial composition has been supported by several clinical studies investigating the relationship between different gut microbiota characteristics and clinical benefits (Supplemental Table 1). 2022,2443 Most of these studies focused on NSCLC, melanoma, and hepatocellular carcinoma, where alpha diversity and some specific gut microbiome constituents have been associated with successful treatment with ICIs, such as Bifidobacterium species, Lactobacillus species, Akkermansia species, Faecalibacterium species, Firmicutes species, and Lachnospiraceae. A favorable gut microbiome improves effector T-cell function in the peripheral and tumor microenvironment (TME).…”
Section: The Gut Microbiota Is Closely Related To the Efficacy Of Icismentioning
confidence: 99%